Pharmacological Properties of Fructooligosaccharides Modulates the Lipopolysaccharide-Induced Gastrointestinal Tract Inflammation in Mice - Shreya (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: The gut is a neuroendocrine-immune organ, vulnerable to stress, and toxic agents, including lipopolysaccharide (LPS) leading to gut dysbiosis and inflammation. The aim of present study was to evaluate the pharmacological properties of prebiotic fructooligosaccharides (FOS) against the LPS-induced gut inflammation in mice. Materials and Methods: The Swiss albino mice (female, 8 weeks) were divided into following four groups (n = 6/group): Group-I/Control: received saline (0.9% NaCl), (II) Group-II/LPS (1 mg/kg for 5 days, intraperitoneal), Group-III/LPS+FOS (LPS 1 mg/kg for 5 days followed by FOS 2 g/kg for 28 days), and Group-IV/FOS (FOS 2 g/kg for 28 days, through oral gavaging). Results: The LPS exposure significantly decreased the body and gut weight compared to control which, after the FOS treatment, increased to control level. In LPS-exposed mice, the decreased of gut associated superoxide dismutase and catalase activity was enhanced and normalized by FOS. Similarly, LPS-induced the pro-inflammatory cytokines IL-6 and TNF-α level were also decreased to control level after FOS treatment. Moreover, LPS exposure caused various histopathological alterations in gut, such as lesions of epithelial layer, edema of villi, and disruption of goblet cells, in which FOS modulated. Conclusion: The pharmacological prebiotic FOS shows the anti-oxidative, anti-inflammatory properties which modulated the LPS-induced gut toxicity by decreasing inflammation and oxidative stress and improving histological architecture.